Career performance trajectories of professional Australian football players - Sullivan, C.; Kempton, T.; Ward, P.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To develop position-specific career performance trajectories and determine the age of peak performance of professional Australian Football players. Methods: Match performance data (Australian Football League [AFL] Player Rank) were collected for Australian Football players drafted via the AFL National Draft between 1999 and 2015 (N = 207). Players were subdivided into playing positions: forwards (n = 60; age 23 [3] y), defenders (n = 71; age 24 [4] y), midfielders (n = 58; age 24 [4] y), and ruckmen (n = 18; age 24 [3] y). Linear mixed models were fitted to the data to estimate individual career trajectories. Results: Forwards, midfielders, and defenders experienced peak match performance earlier than ruckmen (24-25 vs 27 y). Midfielders demonstrated the greatest between-subjects variability (intercept 0.580, age 0.0286) in comparison with ruckmen, who demonstrated the least variability (intercept 0.112, age 0.005) in AFL Player Rank throughout their careers. Age had the greatest influence on the career trajectory of midfielders (ß [SE] = 0.226 [0.025], T = 9.10, P < .01) and the least effect on ruckmen (ß [SE] = 0.114 [0.049], T = 2.30, P = .02). Conclusions: Professional Australian Football players peak in match performance between 24 and 27 years of age with age, having the greatest influence on the match performance of midfielders and the least on ruckmen.